2021
DOI: 10.1186/s12905-021-01225-4
|View full text |Cite
|
Sign up to set email alerts
|

Technology as the key to women’s empowerment: a scoping review

Abstract: Background Information and communications technologies (ICTs) have empowered people to communicate and network at a global scale. However, there is lack of in-depth understanding of the use of ICTs for women's empowerment. This study examines how the concept empowerment is defined, utilized and measured in research studies, the existing evidence on the use of ICTs for women’s empowerment and the gaps in knowledge at the global level. Methods The au… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Most studies have supported that ICT‐related technologies are innovative practices that help empower women (e.g., Chun & Tang, 2018; Crittenden et al, 2019; Mackey & Petrucka, 2021; Rajkhowa & Qaim, 2022b; Sarker, Biswas, Anwar, Stillman, & Oliver, 2021; Sekabira & Qaim, 2017; Shirazi, 2012; Zheng & Lu, 2021). For example, Sekabira and Qaim (2017) showed that mobile phone use is positively associated with women's empowerment in Uganda.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have supported that ICT‐related technologies are innovative practices that help empower women (e.g., Chun & Tang, 2018; Crittenden et al, 2019; Mackey & Petrucka, 2021; Rajkhowa & Qaim, 2022b; Sarker, Biswas, Anwar, Stillman, & Oliver, 2021; Sekabira & Qaim, 2017; Shirazi, 2012; Zheng & Lu, 2021). For example, Sekabira and Qaim (2017) showed that mobile phone use is positively associated with women's empowerment in Uganda.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Information and communication technologies (ICTs), such as the internet, televisions, mobile phones, and smartphones, enable users to obtain information on a global scale and communicate with others efficiently (Mackey & Petrucka, 2021; Min, Liu, & Huang, 2020; Yu & Cui, 2019; Zhu, Li, Gong, & Jinghong, 2022). ICT applications have been proven to improve rural household welfare by, for example, transforming agricultural production and increasing household income (Dzanku & Osei, 2022; Min et al, 2020; Zheng & Ma, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the operational definition of autonomy, several studies have described differences in its composition and methods of measurement. However, there are common components that would help to delimit the necessary aspects of women to be autonomous, such as their participation in economic decision-making in the home, free transit, and health, as well as negative attitudes towards violence [ 13 , 15 , 16 ]. While the terms autonomy and women’s empowerment may be interchangeable, there are differences between their definitions [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the extent of surviving in the current COVID19 business worl [ 35 ], show possible business development possibilities through the use of ICT. Further, gender roles in society can also drive health outcomes [ 21 ]. For those countries where gender gaps in health are shaped by individual and societal norms that tend to undervalue women’s health, relevant interventions which include ICT platforms for effective, innovative, and faster dissemination of messages are needed to reinforce the importance of women and girls for the reduction in health gaps [ 36 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…(; However, ICT can potentially affect various other aspects of public welfare like health [ 17 , 18 ] and gender empowerment [ 8 , 19 , 20 ]. [ 21 ] argue that on-hand access to various computer sites within the community or in schools is one of the effective ways to close the gap in accessibility and usage of ICT, which does not only aid in enhancing the status of the girls and women, but also boosts societal empowerment, equality, and development. [ 22 24 ] examine the use of information and communication technology, including mobile use for boosting health efficiency and patient care.…”
Section: Introductionmentioning
confidence: 99%